Mind, meaning, and reality : essays in philosophy - Mellor, D H. (Oxford University Press, 2012)
"'Mind, Meaning, and reality' contains fifteen philosophical papers by D. H. Mellor, including a new defence of 'success semantics', and an introduction arguing that metaphysics can and need only be justified by doing it and not by a 'meta-metaphysics', which it needs no more than physics needs metaphysics. The papers are grouped into three parts. Part I is about how the ways we are disposed to act fixes what we believe and what we use language to mean. Part II is about what there is: the reality of dispositions: what makes beliefs and sentences true; why there is only one universe; and how social groups, and other things composed of parts, are related to the people and other things that constitute them. Part III is about time, and includes discussions of twentieth-century developments in the philosophy of time; why Kant was right about tense, even though he was wrong about time; why forward time-travel is trivial and backward time travel impossible; and what gives time its direction"--Publisher's description, p. [4] of dust jacket.